Ezra Pound and classical Chinese poetry (Philology, 2026)
Ezra Pound’s engagement with classical Chinese poetry represents a pivotal moment in the development of modern poetry. This study explores how Pound’s use of Chinese ideograms and Confucian philosophy in The Cathay and The China Cantos revolutionized Western poetic forms, creating a bridge between Eastern and Western literary traditions. Through an interdisciplinary approach that combines literary analysis, historical contextualization, and cultural interpretation, this study sheds light on Pound’s enduring legacy as a modernist innovator. By examining Pound’s imagist and vorticist principles, as well as his adaptations of Chinese poetry, this research contributes to a deeper understanding of the intercultural dialogue that shaped modernism. The findings highlight Pound’s ability to transcend temporal and geographical boundaries, offering new insights into the interplay between Eastern and Western aesthetics in modern poetry.
Keywords: imagism; vorticism; “The Cathay”; “The China Cantos”; ideograms